Global Entrepreneurship Monitor Slovenija 2002: the Slovenian Report : the Winding Road to Entrepreneurial Society - Rebernik, Miroslav; Tominc, Polona; Glas, Miroslav; Pšeničny, Viljem (University of Maribor Press, 2004)
The research confirmed the provisional findings of Slovenian researchers of entrepreneurship that Slovenia is not yet functioning as an entrepreneurial society. There is still no social consensus on the need for coordinated action by entrepreneurs and government and on the creation of conducive environment in which as many new firms as possible come into being while existing ones have ambitions to grow and develop. The fundamental challenge that research poses to Slovenia is clear, i.e. how to install a clear vision for Slovenia’s long-term development as an entrepreneurial society and create a conducive environment so that as many people as possible become entrepreneurs? The results of the research showed that Slovenia has a long way to go to realize its ambitions and establish itself in the European Union, as a progressive, innovative and entrepreneurial society. An understanding of the role of entrepreneurship is crucial to achieving this aim. The first part of the monograph reviews the development of entrepreneurship in Slovenia since it became a country in its own right, and the second gives an overview of the activity of existing firms in the previous year.